2022
DOI: 10.33087/jiubj.v22i1.1950
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Resiko yang Mempengaruhi Kejadian Stroke: Sebuah Tinjauan Sistematis

Abstract: Stroke causes demage to the brain that appears suddenly, progressively and rapidly due to a non traumatic cerebral blood circulation disorder, vision. The purposse of this study was to determine the factors that influence the risk of stroke. The research design included in this systematic review used a research design, namely quantitative methods. Based on the results of a systematic review from articles, it was found that the risk factors that in fluence the occurrence of stroke are gender, age, education lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
(11 reference statements)
1
1
0
3
Order By: Relevance
“…Hypertension here is one of the factors that cause a stroke. This study is in line with previous research, which stated that gender, age, education level, history of hypertension, blood cholesterol levels, obesity, coronary heart disease, smoking habits, consuming foods high in salt, and lack of physical activity are factors that can cause heart disease strokes (Utama & Nainggolan, 2022).…”
Section: Resultssupporting
confidence: 92%
“…Hypertension here is one of the factors that cause a stroke. This study is in line with previous research, which stated that gender, age, education level, history of hypertension, blood cholesterol levels, obesity, coronary heart disease, smoking habits, consuming foods high in salt, and lack of physical activity are factors that can cause heart disease strokes (Utama & Nainggolan, 2022).…”
Section: Resultssupporting
confidence: 92%
“…Knowledge about stroke risk factors could relieve stroke onset that may occur without symptoms. A review article by Utama & Nainggolan (2022) found a lack of awareness about stroke causal factors and excellent living behavior in the community triggered the repeated onset 54 .…”
Section: Questionsmentioning
confidence: 99%
“…Makin parah stroke yang dialami pasien, makin tinggi tingkat ketergangungannya dan hal ini menyebabkan keluarga penderita menjadi sulit untuk melakukan kegiatan diluar pendampingan [10]. Serangan stroke yang terjadi seringkali mendadak [11], sehingga keluarga perlu beradaptasi secara cepat. Namun pada kenyataannya, keluarga pasien seringkali tidak siap dengan kondisi melayani kebutuhan pasien setiap saat, sementara keluarga pasien masih memiliki kegiatan rutin yang perlu dikerjakan.…”
Section: Pendahuluanunclassified